Health information and health outcomes: An application of the regression discontinuity design to the 1995 UK contraceptive pill scare case - Emilia Del Bono; Marco Francesconi; Nicky G. Best (University of Essex, Institute for Social and Economic Research (ISER), 2011)
This paper provides a general formulation of the regression discontinuity (RD) design and applies this method to analyse the effects of the 1995 UK pill scare. We show that in the five months following a health warning on the third generation pill, conception rates rose by more than 7%, abortion rates shot up by more than 9%, and birth rates increased by 6-7%. By contrast, no or small effects were found on the resulting babies' general health, with the exception of a reduction in the incidence of congenital anomalies. Heterogeneity by mother's age and social class was very pronounced, with most of the effects being experienced by women aged less than 25 and of lower socioeconomic status.
Keywords: C21; D8; I12; J13; 330; regression discontinuity; contraception; fertility; birth weight; health warnings; effect of the media; Gesundheitsversorgung; Informationsversorgung; Empfängnisverhütungsmittel; Großbritannien